Texting and Educating on Lifestyle Therapy: A Pilot Study in a Spanish-Speaking Population in North Carolina - Ina Liu; Madison Jones; Sarah Anderson; Catherine Feng; Frank Tillman; Macary Marciniak (Journal of Student-Run Clinics, 2018)
Background: Cardiovascular disease is a leading cause of death in Hispanic populations, largely due to the prevalence of risk factors such as diabetes and hypertension. Literature supports the use of mobile technology, particularly text messaging, as a nontraditional means to provide targeted health coaching and positively impact cardiovascular health.Methods: The primary objective of this prospective cohort study was to determine the impact of an educational texting program on participants’ blood pressure and confidence in managing their health. A total of 32 participants for this study were recruited via six weekly announcements during the Spanish Mass at a Catholic Church. Eligible patients were 18 years or older, owned a mobile phone with unlimited text messages, and provided informed consent. Following study enrollment, participants completed a pre-survey that described demographic characteristics, cardiovascular-related medical conditions, preference for English or Spanish messages, and confidence in managing their own health; investigators recorded the participants’ blood pressure at baseline. Participants received two messages per week focused on lifestyle modifications for 20 weeks. At study conclusion, a total of 7 participants completed a post-survey assessing participant’s perception of the program and a final blood pressure was recorded. The Siegel-Tukey was used to assess pre- and post-surveys; Wilcoxon signed-rank assessed pre- and post-blood pressure measurements.Results: There were no differences in confidence measured before and after intervention. Participants who completed the post-survey found the messages to be helpful, ranking the messages 9/10 in terms of helpfulness, and 86% expressed interest in continuing their enrollment. There was a decrease in systolic blood pressure from pre-hypertensive to normal range (131 to 118 mmHg).Conclusions: This pilot study exemplifies the potential benefits of a text messaging platform to provide health coaching.